Measuring quality in community nursing: a mixed-methods study - Sue Horrocks; Katherine Pollard; Lorna Duncan; Christina Petsoulas; Emma Gibbard; Jane Cook; Ruth McDonald; Lesley Wye; Pauline Allen; Pete Husband; Lizanne Harland; Ailsa Cameron; et al. (Health Services and Delivery Research, 2018)
Background: High-quality nursing care is crucial for patients with complex conditions and comorbidities living at home, but such care is largely invisible to health planners and managers. Nursing care quality in acute settings is typically measured using a range of different quality measures; however, little is known about how service quality is measured in community nursing. Objective: To establish which quality indicators (QIs) are selected for community nursing; how these are selected and applied; and their usefulness to service users (patients and/or carers), commissioners and provider staff. Design: A mixed-methods study comprising three phases. (1) A national survey was undertaken of ‘Commissioning for Quality and Innovation’ indicators applied to community nursing care in 2014/15. The data were analysed descriptively using IBM SPSS Statistics 20.0 (IBM Corporation, Armonk, NY, USA). (2) An in-depth case study was conducted in five sites. Qualitative data were collected through observations, interviews, focus groups and documents. A thematic analysis was conducted using QSR NVivo 10 (QSR International, Warrington, UK). The findings from the first two phases were synthesised using a theoretical framework to examine how local and distal contexts affecting care provision impacted on the selection and application of QIs for community nursing. (3) Validity testing the findings and associated draft good practice guidance through a series of stakeholder engagement events held in venues across England. Setting: The national survey was conducted by telephone and e-mail. Each case study site comprised a Clinical Commissioning Group (CCG) and its associated provider of community nursing services. Participants: Survey – 145 (68.7%) CCGs across England. Case study: NHS England national and regional quality leads (n = 5), commissioners (n = 19), provider managers (n = 32), registered community nurses (n = 45); and adult patients (n = 14) receiving care in their own homes and/or carers (n = 7). Findings: A wide range of indicators was used nationally, with a major focus on organisational processes. Lack of nurse and service user involvement in indicator selection processes had a negative impact on their application and perceived usefulness. Indicator data collection was hampered by problematic information technology (IT) software and connectivity and interorganisational system incompatibility. Front-line staff considered indicators designed for acute settings inappropriate for use in community settings. Indicators did not reflect aspects of care, such as time spent, kindness and respect, that were highly valued by front-line staff and service user participants. Workshop delegates (commissioners, provider managers, front-line staff and service users, n = 242) endorsed the findings and drafted good practice guidance. Limitations: Ongoing service reorganisation during the study period affected access to participants in some sites. The limited available data precluded an in-depth documentary analysis. Conclusions: The current QIs for community nursing are of limited use. Indicators will be enhanced by involving service users and front-line staff in identification of suitable measures. Resolution of connectivity and compatibility challenges should assist implementation of new IT packages into practice. Modifications are likely to be required to ensure that indicators developed for acute settings are suitable for community. A mix of qualitative and quantitative methods will better represent community nursing service quality. Future work: Future research should investigate the appropriate modifications and associated costs of administering QI schemes in integrated care settings. Funding: The National Institute for Health Research Health Services and Delivery Research programme.